Efek hipoglikemik tepung komposit (ubi jalar ungu, jagung kuning, dan kacang tunggak) pada tikus diabetes induksi streptozotocin - Carolina Sisca Djunaidi; Dian Rachmawanti Affandi; Danar Praseptiangga (Jurnal Gizi Klinik Indonesia, 2014)
Background: The composite flour (50% sweet potato, 30% corn, and 20% cowpea) had proven that it could substitute 100% wheat flour for biscuit making. Intake of antioxidants, dietary fiber, and protein, had been known to reduce plasma glucose level. Objective: To evaluate the effect of composite flour diet on plasma glucose levels, body weight and food consumption of streptozotocin (STZ)-diabetic rats.Method: Thirty male Sprague-Dawley rats aged ± 2 months (± 200 grams), were divided into three groups of ten rats. They were (1) non-diabetic standard diet (ND-STD), (2) diabetic (65 mg/kg of body weight by STZ induction) standard diet (D-STD), and (3) diabetic composite flour diet (1,5 g/100 g of body weight/day) (D-CFD), for 4 weeks, 3 days after STZ induction. The plasma glucose obtained from GOD-PAP method were determined before induction, after induction and every week during diet intervention.Results: Plasma glucose levels was significantly lower in D-CFD when compared with D-STD (p<0,05). The weight of D-STD was found to be significantly decreased as compared to ND-STD (p<0,05). There were no changes in food consumption of ND-STD, D-STD and D-CFD (p<0,05).Conclusion: The composite flour could reduce plasma glucose level in diabetic rats and did not give negative effects on body weight and food consumption.